Enhancing tax compliance through Coretax: A phenomenological study on SP2DK and audit risk mitigation - Claudia Wanda Melati Korompis; Olivia Yulieta Megi Sardjono; Diana Nova Lintong (AFRE (Accounting and Financial Review), 2026)
This study aims to reveal tax consultants lived experiences in mitigating SP2DK (tax clarification letter issued by the tax authority) and audit risks because of the Coretax implementation. This research employs a descriptive qualitative method with a phenomenological approach. Data were collected through in‑depth, semi‑structured interviews with tax consultants who had direct experience in handling SP2DK and audit cases under the Coretax. All interviews were audio‑recorded, transcribed verbatim, and anonymised to protect participant confidentiality. The transcribed data were analysed using thematic analysis, following the six‑phase procedure proposed by Braun & Clarke (2006). To facilitate systematic coding and theme development, the software Taguette was employed. The implementation of Coretax transforms the mechanism of SP2DK and audit risk mitigation through three main pathways. First, automatic validation and integrated reconciliation features enable tax consultants to perform pre-filing data checks, thereby preventing technical errors at the outset. Second, NIK-based transparency ensures that all transactions are recorded by the tax authority, creating a deterrent effect on non-compliant taxpayers. Third, the integration of SP2DK into the Coretax dashboard accelerates consultant responses because the basis of the tax authority's inquiry is immediately visible.